Kontaminan Telur Soil Transmitted Helminths (STH) Pada Kuku Siswa TK Sari Mekar Banguntapan Yogyakarta - Moh Adit Fatwa; Nunung Sulistyani (SEHATI: Jurnal Kesehatan, 2025)
Soil Transmitted Helminths (STH) are a group of nematodes that cause inflammation in humans known as helminthiasis that occurs through oral infective egg stages and/or penetration of infective larval stages. Empirically, helminthiasis are a disease that is underestimated by the community, but without treatment and prevention it can have a negative impact on children's health, namely the risk of poor academic achievement. This study aims to identify STH egg contaminants in the fingernails of students at Sari Mekar Kindergarten Banguntapan Bantul Yogyakarta. This study is a descriptive study by examining student nail clippings using the sedimentation method. STH egg contamination is determined by finding STH eggs in student nail clippings. The data obtained were analyzed descriptively by calculating the number of positive nail clipping samples contaminated with STH eggs. Data are presented in the form of tables and narratives. The results showed that 0% STH egg contamination in the nail clippings of students at Sari Mekar Kindergarten Banguntapan Bantul Yogyakarta. The conclusion of this study is that no STH egg contaminants were identified in the fingernail of students at Sari Mekar Banguntapan Bantul Yogyakarta.